Interval‐valued probabilistic hesitant fuzzy set and its application in the Arctic geopolitical risk evaluation. Issue 4 (11th November 2018) - Song, Chenyang; Zhao, Hua; Xu, Zeshui; Hao, Zhinan
Abstract: The probabilistic hesitant fuzzy set (PHFS) associates the probability with the hesitant fuzzy set (HFS), which has been proposed to improve the granularity of the HFS and can remain more information, is significant to solve the multicriteria group decision‐making (MCGDM) problems when the decision makers fail to provide their preferences completely. To express the probability information existing in the hesitancy more conveniently, we propose a generalized form of P‐HFS named interval‐valued probabilistic hesitant fuzzy set (IVPHFS). In addition, we define some basic operation laws and aggregation operators of IVPHFSs. Based on which, we provide an efficient approach to deal with the practical MCGDM problems by IVPHFSs aggregation operators under the interval‐valued probabilistic hesitant fuzzy environment. Last but not least, we apply the proposed approach to the research of the Arctic geopolitical risk evaluation. The method based on the score function of the probabilistic dual hesitant fuzzy set is also introduced for comparison. The comparing results demonstrate that our approach is more reasonable and logical.